Menganalisis Semiotika Bahasa Gaul Dikalangan Siswa Sekolah Dasar : Implikasi Terhadap Pembelajaran Bahasa Indonesia - Fitri Muliani Halawa; Marina Juni Gulo (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study uses a qualitative library method aimed at analyzing the use of slang from a semiotic perspective among elementary school students and its implications for Indonesian language learning. The slang frequently used by students has certain symbols, meanings, and signs that reflect group identity, social dynamics, and the cultural development of early adolescence. In this context, slang functions not only as a means of communication but also as a means of self-expression and building social relationships among peers. The use of slang among elementary school students creates a space for them to interact and understand each other, as well as strengthen social bonds within their group. This study examines various literature and previous research results on semiotic theories proposed by Ferdinand de Saussure and Charles Sanders Peirce. These theories serve as an important foundation in understanding the linguistic signs and meanings behind the use of slang. However, the uncontrolled use of slang can potentially obscure the rules of standard Indonesian. If not addressed with an appropriate pedagogical approach, this can disrupt the learning process and students' understanding of formal Indonesian. Therefore, it is important for educators to understand the dynamics of slang use among students in order to manage and direct its use in learning contexts. This way, students will not only be able to communicate well in slang but also be able to apply standard Indonesian language rules in appropriate situations, enabling them to become effective and competent communicators in today's global era. This research is expected to provide deeper insight into the importance of understanding slang in educational contexts, as well as encourage the development of more innovative and relevant teaching methods to meet the needs of students in the modern era.